2012
DOI: 10.1039/c1cy00404b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient cyclic carbonate synthesis catalyzed by zinc cluster systems under mild conditions

Abstract: An efficient catalytic system of a zinc cluster and tetrabutylammonium iodide (TBAI) was developed for cyclic carbonate synthesis from epoxides and carbon dioxide (CO 2 ) without the use of any organic solvents under very mild conditions (25 1C, 1 atm), even in the presence of impurities such as water and air. Electrophilicity of the central Zn(II) ion, the number of trifluoromethyl groups, nucleophilicity and leaving ability of the anion of alkylammonium salts, and various reaction parameters have a great eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…Studies on the cycloaddition of CO 2 to epoxides catalysed under mild conditions by Al-and Zn-complexes have shown that these catalysts are compatible with the presence of O 2 in the reaction environment. 24b, 34,35 Also in our case, only a slight decrease in the performance of the catalyst has been observed by replacing Ar with O 2 as a gas carrier (Chart 1, Entries 5, 7). These observations suggest that the title reaction is generally O 2 -tolerant, at least when carried out under mild conditions.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Studies on the cycloaddition of CO 2 to epoxides catalysed under mild conditions by Al-and Zn-complexes have shown that these catalysts are compatible with the presence of O 2 in the reaction environment. 24b, 34,35 Also in our case, only a slight decrease in the performance of the catalyst has been observed by replacing Ar with O 2 as a gas carrier (Chart 1, Entries 5, 7). These observations suggest that the title reaction is generally O 2 -tolerant, at least when carried out under mild conditions.…”
Section: Resultsmentioning
confidence: 85%
“…Water can potentially have a detrimental effect on this reaction by leading to the formation of (poly)glycols and/or by affecting the stability of metal-based catalyst. Nevertheless, organometallic catalysts such as an aluminium aminotrisphenolate complex 35 and a tetranuclear Zn cluster 36 have been reported as robust and selective catalysts for the cycloaddition of CO 2 to epoxides in the presence of water. The addition of water has even been found to have a promoting effect on the title reaction catalysed by potassium iodide and ionic liquids by activation of the substrate via H-bond formation.…”
Section: Resultsmentioning
confidence: 99%
“…([FeTPhOA] 2 ,T able 5, entry 14); [38] ab imetallic Fe III complex reported by Williams and co-workers, [39] bearing at etraimino(amino)diphenol macrocyclic ligand ([LFe 2 Cl 4 ] 2 , Ta ble 5, entry 15) and at etranuclear Zn 4 (OCOCF 3 ) 6 Oc omplex reportedb yM ashima and co-workers(Ta ble5,e ntry 16). [40] Comparison between the TOF values reported in Table 5f or the different catalytic pairs shows that simple Nb and Yh alides compounds are high-performing catalysts for this reaction even when compared to more sophisticated, polymetallic catalytic systems bearing elaborated organic ligands.…”
Section: Cycloadditions Of Co 2 To Epoxidesmentioning
confidence: 94%
“…Several homogeneous and heterogeneous catalysts have been explored for this reaction. Homogeneous catalysts include polyoxometalates (POMs) [4], complexes of transition metals (Zn, Al, Cr, Co, Cu, Ni, and Sn) salen porphyrin and phthalocyanine [5][6][7], ionic liquids [8], and quaternary ammonium salts [9]. Although many homogeneous catalysts were found to be effective at low pressure and temperature [6,7], the difficult and costly separation of the catalysts from the reaction products represents a serious drawback to their application.…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneous catalysts include polyoxometalates (POMs) [4], complexes of transition metals (Zn, Al, Cr, Co, Cu, Ni, and Sn) salen porphyrin and phthalocyanine [5][6][7], ionic liquids [8], and quaternary ammonium salts [9]. Although many homogeneous catalysts were found to be effective at low pressure and temperature [6,7], the difficult and costly separation of the catalysts from the reaction products represents a serious drawback to their application. Consequently, various heterogeneous catalysts, such as metal oxides [10,11], immobilized complexes or ionic liquids [12][13][14], titanosilicates [15], metal-organic frameworks [16][17][18][19], and zeolites [19], were tested.…”
Section: Introductionmentioning
confidence: 99%